The Effect of Land Unit Elimination on The Conservation Activity Plan at Air Bengkulu Watershed, Bengkulu Province - Bambang Sulistyo; Muhammad Faiz Barchia; Kanang Setyo Hindarto; Noviyanti Listyaningrum (Faculty of Geography, Universitas Gadjah Mada, 2020)
To enable conservation of degraded land requires Map of Conservation Activity Plan (CAP). The map is established based on a model developed by the then Ministry of Environment and Forestry. One step to analyze the CAP is land unit elimination (LUE) having area of < 1 cm2. This study aimed to determine the effect of LUE on the CAP at Air Bengkulu Watershed. Maps used for input to CAP are EHL (Erosion Hazard Level), Soil Depth, Slope, Population Pressure, and the Recommended Landuse, whereas to calculate EHL requires R, K, LS, C, and P Factors. CAP Map as a result without involving LUE is compared to the CAP Map with involving LUE. The research result showed that the LUE influences on the change of the recommended of the CAP up to 77.6% of the total area of the study, either in engineering recommended or in vegetatively recommended conservation, while the rest (22.4%) were unchanged.